2019
DOI: 10.1111/asj.13267
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary reduced mineral elements and coated cysteamine supplementation on bacterial diversity in the ileum of finishing pigs

Abstract: This study was conducted to investigate the effects of different levels of dietary partial MEs and coated cysteamine (CC) supplementation on gut microbiota in finishing pigs. Results showed that whittling down dietary partial MEs (Cu, Fe, Zn, Mn) by 20% and 40% had little effect on the microbial diversity, community structure, and bacterial relative abundance in the ileum of finishing pigs. Supplementation with 1,600 mg/kg CC also had no obvious effect on the microbial diversity, community structure, and bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…A recent study has shown that some bacteria play a potential role in pigment synthesis [24]. At the same time, it has been reported that cysteamine supplementation changed bacteria composition in the intestine [25] and regulated gut pathogenic bacteria [26]. Additionally, cysteamine supplementation is considered to protect against the oxidation of pigments [27].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that some bacteria play a potential role in pigment synthesis [24]. At the same time, it has been reported that cysteamine supplementation changed bacteria composition in the intestine [25] and regulated gut pathogenic bacteria [26]. Additionally, cysteamine supplementation is considered to protect against the oxidation of pigments [27].…”
Section: Discussionmentioning
confidence: 99%